DEVELOPMENT OF COGNITIVE INDEPENDENCE OF STUDENTS IN TEACHING INFORMATICS BASED ON NON-LINEAR TECHNOLOGIES OF EDUCATION (Intent Research Scientific Journal, 2023)
This article discusses the development of cognitive independence of students in the teaching of informatics based on non-linear technologies of education. In addition, the role of knowledge in modern conditions, the fact that it has become the main factor in the development of society. And in turn, it is noted that this serves as a strong incentive for the development of more effective educational technologies and their introduction into educational practice.